Mengukir Jembatan Ilmu dan Kasih: Mahasiswa Pendidikan Fisika Mengajarkan Ilmu Fisika yang menyatu dengan Perjalanan Ilmu Ramadhan di Tengah Kehidupan Anak-Anak Bawah Jembatan Flyover Cakrawala - Elfani Zidni Ilma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Semarang, the capital of Central Java, is one of the big cities in Indonesia. However, the city still experiences significant education gaps. Moved by concern and enthusiasm for educating the nation, several physics education students at UIN Walisongo Semarang University together with the login house community carried out a joint learning program by introducing physics with children under the Semarang Cakrawal flyover bridge. This activity aims to improve children's knowledge and skills in physics subjects. This activity is not only about documenting a joint learning program but it is a moral movement to fight for the right to education for all children in Indonesia. This research was conducted in the urban area under the Cakrawala Flyover Bridge, Tawangsari, West Semarang. The method used in this service activity uses a classical approach. Children's enthusiasm and motivation for learning physics seems to be getting higher after being given motivation and fun learning methods from physics students.